Maqashid Syariah Perspective: Implementation of Ta’widh and Ta’zir in Islamic Banking in the View of the Fatwa of the Indonesian Ulema Council - Khristina Sri Prihatin; Asmuni Asmuni (Faculty of Law, Universitas Pekalongan, 2025)
The DSN-MUI Fatwa regulates the application of ta’widh and ta’zir by taking into account sharia principles, ensuring that the compensation mechanism and sanctions do not contain elements of usury or injustice. From the perspective of maqashid sharia, the application of ta’widh and ta’zir aims to protect property (hifzh al-mal) and uphold justice in transactions, thus supporting the achievement of the main objectives of sharia. This research shows that the DSN-MUI fatwa provides a clear legal basis for the implementation of these two concepts, maintaining a balance between the protection of the rights of transacting parties and the continuity of fair and sustainable Islamic banking practices. Using a descriptive qualitative approach and normative analysis, this study explores how MUI fatwas regulate the application of ta’widh and ta’zir and how their application is relevant to the main objectives of maqashid sharia, namely safeguarding wealth, justice and social balance in the Islamic economy